3D Research Challenges in Cultural Heritage: A Roadmap in Digital Heritage Preservation - (:unkn) unknown (My University, 2014)
This book contains selected contributions from some of the most renowned researchers in the field of Digital Heritage and 3D representation of the Past, based in large part on invited presentations from the workshop “Computational Geometry and Ontologies for Cultural Heritage 3D Digital Libraries: What are the future alternatives for Europeana?” which was held in conjunction with the International Conference on Cultural Heritage EuroMed2012 (www.euromed2012.eu) on the island of Cyprus in October 2012. This was the official event of the Cyprus Presidency of the Council of the European Union on Progress in Cultural Heritage Preservation. The aim of this book is to provide an insight to ongoing research and future directions in this novel, continuously very promising and multi-disciplinary evolving field, which lies at the intersection of digital heritage, engineering, computer science, mathematics, material science, architecture, civil engineering and archaeology.
Keywords: Cultural heritage; Behavioral animation; 3D imaging; Web-based graphics; 3D printing; Digital 3D models